2021
DOI: 10.3390/sym13112231
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity on Neutral-Type Inertial Neural Networks Incorporating Multiple Delays

Abstract: The classical Hopefield neural networks have obvious symmetry, thus the study related to its dynamic behaviors has been widely concerned. This research article is involved with the neutral-type inertial neural networks incorporating multiple delays. By making an appropriate Lyapunov functional, one novel sufficient stability criterion for the existence and global exponential stability of T-periodic solutions on the proposed system is obtained. In addition, an instructive numerical example is arranged to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The existence and exponential stability of the periodic solution is one important and interesting topic in the dynamical analysis of neutral neural networks. Recently, in [34], the existence and global exponential stability of T-periodic solutions of neutral-type inertial neural networks with multiple delays was investigated using the Lyapunov functional. It was found that the coefficients and the time delays are bounded constant, and the external inputs are periodic functions.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence and exponential stability of the periodic solution is one important and interesting topic in the dynamical analysis of neutral neural networks. Recently, in [34], the existence and global exponential stability of T-periodic solutions of neutral-type inertial neural networks with multiple delays was investigated using the Lyapunov functional. It was found that the coefficients and the time delays are bounded constant, and the external inputs are periodic functions.…”
Section: Remarkmentioning
confidence: 99%
“…It was found that the coefficients and the time delays are bounded constant, and the external inputs are periodic functions. Consequently, the method proposed in [34] is not applicable to NINN with unbounded proportional delays and variable coefficients. Furthermore, in [35,36], almost periodic solutions for various neural networks with neutral type proportional delays and D operators were investigated by means of Banach fixed point theorem and differential inequality technique.…”
Section: Remarkmentioning
confidence: 99%
“…Si, Xie and Lie [27] investigated the global exponential stability of recurrent neural networks with piecewise constant arguments and neutral terms subject to uncertain connection weights. For more results of neutral-type neural networks, see, e.g., [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%